2019
DOI: 10.1103/physrevlett.123.255101
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Electromagnetic Electron Holes and Evidence of Cherenkov Whistler Emission

Abstract: We report observations of electromagnetic electron holes (EHs) in the plasma sheet boundary layer made by the Magnetospheric Multiscale mission. We use multi-spacecraft analysis to quantify the magnetic field contributions of three mechanisms: the Lorentz transform, electron drift within the EH, and Cherenkov emission of whistler waves. Our results show that EHs with speeds approaching half the electron Alfvén speed excite whistler waves via the Cherenkov mechanism. The resonant whistlers are strongly damped a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…The blue shaded area in the figure represents the EDR. Graham, Vaivads, Contel, et al (2019), it is found that the perpendicular electric field with bipolar structure accounts for about 25% in 336 EHs. Therefore, it is not accidental to observe the bipolar 1 E in our event.…”
Section: Mms Observations and Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue shaded area in the figure represents the EDR. Graham, Vaivads, Contel, et al (2019), it is found that the perpendicular electric field with bipolar structure accounts for about 25% in 336 EHs. Therefore, it is not accidental to observe the bipolar 1 E in our event.…”
Section: Mms Observations and Simulationsmentioning
confidence: 99%
“…In the sub-period 22:34:03.28-22:34:03.32 UT, the parallel electric field E || has several bipolar structures, which is the typical characteristics of electron holes (EHs;Lu et al, 2008Lu et al, , 2005Matsumoto et al, 2003;Omura et al, 1996;Wu et al, 2010), and the corresponding perpendicular electric field 1E also has bipolar structure (Figure3A2). Although the unipolar structures of the perpendicular electric field are more often observed in the EHs, the perpendicular electric field with a bipolar structure is also detected by satellite observations(Andersson et al, 2009;Matsumoto et al, 2003;Steinvall, Khotyaintsev, Graham, Vaivads, Contel, et al, 2019;Vasko et al, 2017;Wang et al, 2013Wang et al, , 2014. InSteinvall, Khotyaintsev,…”
mentioning
confidence: 97%
“…In particular, the MMS measurements have already allowed resolving the three‐dimensional structure of electron phase space holes (Holmes et al., 2018; Steinvall, Khotyaintsev, Graham, Vaivads, Lindqvist, et al, 2019; Tong et al., 2018), measuring the dearth of the phase space density of trapped electrons (Mozer et al., 2018), and resolving electromagnetic structure of subrelativistic electron phase space holes (Le Contel et al., 2017). In addition, the measurements of the MMS spacecraft allowed detecting whistler waves emitted by electron phase space holes via the Cherenkov resonance (Steinvall, Khotyaintsev, Graham, Vaivads, Le Contel, et al, 2019) and identifying electron acceleration and thermalization associated with electron phase space holes (Khotyaintsev et al., 2020; Mozer, Agapitov, Artemyev, et al, 2016; Mozer, Artemyev, Agapitov, et al, 2016; Norgren et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, until now there were no observations supporting this picture. Recent MMS observations in the magnetotail show existence of EHs with associated righthand polarized magnetic components consistent with whistlers (Steinvall et al, 2019a). The magnetic signature is rather localized to the EHs, i.e., no freely propagating whistler is observed as suggested by simulations (Goldman et al, 2014).…”
Section: Whistlersmentioning
confidence: 85%